Empowered Or Beleaguered? Principals’ Accountability Under New York City’s Diverse Provider Regime - Shipps, Dorothy (Education Policy Analysis Archives, 2012)
By 2008, New York City’s school governing regime contained two market-creation policies. Each reshaped principal incentives. One closed large high schools, replacing them with four-to-eight small schools. Another replaced uniform district-provided services with eleven School Support Organizations (SSOs). Both aimed to empower principals with new discretion. This interview study of a small, stratified random sample of high school principals uses mixed methods to analyze 241 incidents detailing their reactions. Guiding questions include whether principals experienced the policies as empowering. Findings show that two thirds of the principals felt beleaguered rather than empowered; incentives appeared insufficient to provide them with unambiguous direction and confidence in their own decisions. The study concludes by considering what additional resources might be needed to expand the one third who felt empowered into a majority. ﻿<!--StartFragment--><!--EndFragment-->